The Invention of pornography: obscenity and the origins of modernity, 1500 - 1800 - Hunt, Lynn (Zone Books, 1993)
In America today the debate over the censorship of pornography continues to call into question the values of a modern, democratic culture. The Invention of Pornography, a groundbreaking collection of critical essays, traces the history and uses of pornography in early modern Europe, offering for the first time the historical perspective crucial to understanding current controversies in politics and the arts.